A transference inequality for rational approximation to points in geometric progression - Champagne, Jérémy; Roy, Damien (Hardy-Ramanujan Journal, 2020)
We establish a transference inequality conjectured by Badziahin and Bugeaud relating exponents of rational approximation of points in geometric progression.